Pain in neonates: A literature review from 1998 to 2008 Neonatal pain: literature review from 1998 to 2008 - Maria Cristina Pauli da Rocha; Lisabelle Mariano Rossato (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This study aimed to conduct a review of scientific literature on neonatal pain, from keywords relevant to the subject, in databases Lilacs and Medline and Pubmed. It was selected 30 articles and its analysis understood 5 themes: 1. Stimulation painful to neonate, 2. Expression of neonatal pain, 3. Instruments of assessment of neonatal pain; 4. Methods of control and relief of pain neonatal, 5. Perception; assessment and management of neonatal pain. The reports demonstrate the lacks in practice such as changes in types of evaluation and management of pain, inconsistencies in the documentation, lack of written rules for the pain and therefore sub treatment of the same. Although the instruments of pain assessment of neonatal are being clinically tested by several researchers, there is a deficiency of published studies that include reports of experience of nurses in the use of such tools in clinical practice in the daily life of neonatal (NICU). Literature review related to neonatal pain. Objectives: to identify scientific articles related to the theme in computerized database - Medline, Lilacs and Cinahl; to identify themes related to neonatal pain. The methodology utilizes research computer and/or manual bibliography. Data were obtained from 32 scientific literatures from 1998 to 2008. Results: studies were published mainly in English. Five themes were identified: painful stimulation to neonates; expression of neonatal pain; assessment instruments of neonatal pain; methods for control and relief of neonatal pain; perception, assessment and management of neonatal pain. Conclusion: the reports revealed gap in care such as wrong methods of pain evaluation and management, inconsistent documentation, absence of written rules leading to sub or mistreatment. Although instruments of pain assessment in neonates are being clinically tested by several researchers, there is a deficiency of published studies (such as nurses experience reports in the use of such tools) in clinical practice in the daily life of neonatal intensive care unit.